Las redes sociales y la perspectiva de los ciudadanos al momento de elegir a su candidato presidencial - Macias Bermeo, Kevin Javier (2021)
The present study reveals as a topic, Social networks and the perspective of citizens when electing their presidential candidate Ecuador 2021 in the Babahoyo canton, which shows through an investigative study the influence that social networks have on the perspective of the citizen at the time of electing one of the participants in the presidential elections, for which it was presented as a general objective, To determine how important is the use of new information technologies through social networks, in electoral political campaigns. For a correct investigation, the use of bibliographic means was carried out, which allowed us to know the different sources of experts and digital media that talk about the subject, as well as pertinent illustrations that helped to deepen the subject and obtain the best results. Among the collection techniques, surveys were used, which were applied to 380 Babahoyense, which showed their criteria for each of the questions posed. For the culmination, the author proceeds to present the conclusions and respective recommendations of the topic, considering relevant points within the investigation.